A second chance—reoperation in patients with failed surgery for intractable epilepsy: long-term outcome, neuropsychology and complications. Issue 4 (8th April 2015) - Grote, Alexander; Witt, Juri-Alexander; Surges, Rainer; von Lehe, Marec; Pieper, Madeleine; Elger, Christian E; Helmstaedter, Christoph; Ormond, D Ryan; Schramm, Johannes; Delev, Daniel
Abstract : Object: Resective surgery is a safe and effective treatment of drug-resistant epilepsy. If surgery has failed reoperation after careful re-evaluation may be a reasonable option. This study was to summarise the risks and benefits of reoperation in patients with epilepsy. Methods: This is a retrospective single centre study comprising clinical data, long-term seizure outcome, neuropsychological outcome and postoperative complications of patients, who had undergone a second resective epilepsy surgery from 1989 to 2009. Results: A total of 66 patients with median follow-up of 10.3 years were included into the study. Fifty-one patients (77%) had surgery for temporal lobe epilepsy, the remaining 15 cases for extra-temporal lobe epilepsies. The most frequent histological findings were tumours (n=33, 50%), followed by dysplasia, gliosis (n=11, each) and hippocampus sclerosis (n=9). The main reasons for seizure recurrence were incomplete resection (59.1%) of the putative epileptogenic lesion. After reoperation 46 patients (69.7%) were completely seizure-free International League Against Epilepsy 1 (ILAE 1) at the last available follow-up. The neuropsychological evaluation demonstrated that repeated losses in the same cognitive domain, that is, successive changes from better to worse performance categories, were rare and that those losses after first surgery were followed by improvement rather than decline. However, reoperations lead to an increased rate of permanent neurological deficits (9%), overall surgical complications (9%) and visual field deficits (67%). Conclusions: Reoperation after failed resective epilepsy surgery led to approximately 70% long-time seizure freedom and reasonable neuropsychological outcome. There is an increased risk of permanent postoperative neurological deficits, which should be taken into consideration when counselling for reoperation.